PERANCANGAN DAN SIMULASI LINEAR QUADRATIC TRACKING PADA SISTEM PENGENDALIAN SUHU PADA PLANT SUHU DISTILASI BIOETANOL - Yusron Nur Aziz; Goegoes Dwi Nusantoro; Muhammad Aziz Muslim (Jurnal Mahasiswa TEUB, 2021)
Bioetanol merupakan salah satu alternatif energi yang dirasa mampu menggantikan energi dengan bahan bakar fosil. Bioetanol dapat dihasilkan dengan cara fermentasi dengan bahan utama yang mengandung kandungan selulosa seperti tetes tebu, tetapi kadar yang dihasilkan sangat rendah. Bioetanol dengan kadar tinggi dapat dihasilkan dengan cara distilasi. Distilasi merupakan proses pemisahan molekul etanol dengan cara dipanaskan pada suhu tertentu. Pada penelitian ini membahas simulasi pengendalian suhu menggunkan 2 kontroler yaitu linear quadratic tracking with model following dan linear quadratic tracking with reference tracking. Pada masalah linear quadratic diperlukan trial dan error matriks bobot Q dan R dengan Bryson’s Rule sebagai acuan. Simulasi dilakukan dengan bantuan software MATLAB (Simulink). Berdasarkan hasil simulasi kontroler LQT with reference tracking memiliki karakteristik respon dengan settling time 6477 detik dan overshoot 4.24% sedangakan kontroler LQT with model following memiliki karakteristik respon dengan settling time 20074 detik tetapi tanpa overshoot. Selain itu simulasi juga dilakukan dengan perubahan set point, pada set point naik dari 60°C-90°C kontroler LQT with reference tracking memiliki nilai settling time 6493 detik dan overshoot 1.39%, sedangkan pada kontroler LQT with model following set point tidak tercapai. Saat sistem disimulasikan dengan set point turun dari 90°C-70°C kontroler LQT with reference tracking memiliki nilai settling time 6492 detik dan overshoot -1.2%, sedangkan pada kontroler LQT with model following set point tidak terpenuhi. Berdasarkan hasil simulasi kontroler LQT with reference tracking memiliki respon keluaran yang lebih baik daripada LQT with model following. Kata kunci: Bioetanol, Distilasi, Kontroler LQT, Simulink, Bryson’s Rule, Model Following, Reference Tracking. ABSTRACT Bioethanol is one among many energy alternatives that presumably can replace fossil fuel-based energy. Bioethanol can be obtained by fermenting things that contain starch and cellulose such as molasses. However, the bioethanol produced from fermentation is low. Bioethanol with high level of content can be obtained by distillation. Distillation is a process of separating ethanol molecule by heat with a certain temperature. This study explores the simulation of temperature control using two controllers i.e. Linear Quadric Tracking (LQT) with model following and Linear Quadric Tracking (LQT) with reference tracking. On the linear quadratic, it is necessary to have the matrix of trial and error with the weight of Q and R while using Bryson’s Rule as the reference. The simulation was conducted using MATLAB (Simulink). According to the result of simulation controller, LQT with reference tracking showed response characteristics of settling time of 6477 secs and overshoot of 4.24%. On the other hand, LQT with model following controller showed response characteristics of settling time of 20074 secs without overshoot. Moreover, the simulation was also conducted by changing the set point. With set point in hand raised from 60°C to 90°C, LQT with reference tracking controller showed settling time value as much as 6493 secs and overshoot of 1.39%. Nonetheless, the set point of LQT with model following controller was not achieved. When the system was simulated by decreasing the set point from 90°C to 70°C, LQT with reference tracking controller had a settling time of 6492 secs and overshoot of -1.25. Whereas the set point of LQT with model following controller was not achieved. According to the simulation, it can be concluded that LQT with reference tracking controller showed better result than the LQT with model following. Keywords: Bioethanol, Distillation, LQT Controller, Simulink, Bryson’n Rule, Model Following, Reference Tracking.